Nontraumatic popliteal pseudoaneurysm: A rare entity with different etiologies - A. Galindo Cordero, Ph; Ferran Pla Sanchez, Ph; Rosa Lopez Perez, Ph; Efren Martel Almeida, Ph; Serguei de Varona Frolov, Ph; Guido Volo Perez, Ph (Journal of Vascular Surgery Cases and Innovative Techniques)
Pseudoaneurysms of the popliteal artery represent a rare vascular pathology. Leaving aside traumatic antecedents, in the presence of sudden swelling of the popliteal region, it is useful to suspect this entity, especially in the presence of infectious processes or connective tissue disorders. We present two cases from our institution where management included surgical intervention and control of the underlying diseases.